Byggkostnader inom mjölkproduktionen - jämförelse av olika stallstorlekar och byggnadstekniska utföranden - Belin, Jeanette (2009)
Investment costs for eight different type housing systems for dairy cows has been calculated in order to compare the building costs as a function of herd size, shelter type and automatization. A commercial calculation programme for building was used and complemented with prices of equipments specific for dairy cow building.